Therapeutic Potential of Decoys for Prostate Cancers: A Review of Recent Updates - Rezaei, Samaneh; Mahjoubin-Tehran, Maryam; Iratni, Rabah; Sahebkar, Amirhossein (Current Medicinal Chemistry, 2024)
Prostate cancer is ranked second among the most common male cancers. Androgen deprivation therapy (ADT) has long been the first-line treatment and the basis for all other therapies, reducing circulating androgens to castration levels and preventing disease development. Nevertheless, ADT monotherapy may not always limit disease development, and even at low testosterone levels, hormone-sensitive prostate cancer will become castration-resistant. Recent research demonstrates that prostate cancer can have a range of potentially actionable genetic abnormalities; no medications that target these variations have yet been shown to elicit therapeutic advantages. Despite their established efficacy in the management of other cancers, advanced genetic or immunological approaches are not regularly used to treat prostate cancer patients. As a result, there is an unmet demand for medicines that offer a better chance of survival than the existing castration- resistance prostate cancer (CRPC) therapy regimens. The use of oligodeoxynucleotides (ODN) and peptides in decoy technology have been developed as novel therapeutic approaches. Decoy ODNs bind to a particular transcription factor with high affinity and may suppress gene transcription. Peptide decoys bind to specific ligands with high specificity and inhibit signaling pathways. Recent evidence supports the notion that these techniques are promising and attractive in the fight against cancer. In the present review, we discuss the use of decoy technology as a novel therapeutic approach against prostate cancer.
Keywords: decoy ODN